Isomerism, Conformation and Molecular Symmetry in Phosphorus Compounds - Prakash Mishra, Shiv; Ojha, S.C.; Pathak, L.P. (Asian Journal of Chemistry, 2010)
The phospha-V-ates and phospha-V-azenes have shown to the stereo- and geometrical isomerism, chair-boat conformation and C3v, C2h and D3h molecular symmetry in their novel structure, which are structurally characterized by X-ray analyses, IR, Raman, 31P NMR and vibrational spectra.